The Influence Of Participative Leadership Style And Communication On Employee Performance At Alfamart Bengkulu City - Elenri, Heni; Irwanto, tito; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2024)
The purpose of this research is to determine the influence of participative leadership style and communication on employee performance at Alfamart, Bengkulu City. The sample in this study was employees at 5 Alfamart stores such as Alfamart Danau, Alfamart Mayjen Sutoyo, Alfamart Museum, Alfamart Pangeran Natadirja and Alfamar Merapi, totaling 31 people. The sampling technique is census. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The results of the research show that the multiple linear regression calculations obtained the multiple linear regression equation Y = 9.219 + 0.416X1 + 0.383X2 + 6.425(e). The coefficient of determination of the Adjusted R square value is 0.465. This means that X1 (participative leadership style) and The F test results show that the significance is 0.000 <0.05. Because the significance level is below 0.05, it shows that together X1 (participative leadership style) and X2 (communication) have a positive and significant influence on performance (Y). The participative leadership style has a positive and significant influence on performance because the significant value is 0.020 < 0.05, communication has a positive and significant influence on performance because the value is 0.037 < 0.05.